Management process of foreign trade and credit department of Bank Asia Limited (Gulshan Branch) - Islam, Sadman Showmik (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.